2003
DOI: 10.1136/pmj.79.929.127
|View full text |Cite
|
Sign up to set email alerts
|

Thalidomide and its derivatives: emerging from the wilderness

Abstract: Forty years on from its worldwide withdrawal, thalidomide is currently undergoing a remarkable renaissance as a novel and powerful immunomodulatory agent. Over the last decade it has been found to be active in a wide variety of inflammatory and malignant disorders where conventional therapies have failed. Recently, considerable progress has been made in elucidating its complex mechanisms of action, which include both anticytokine and antiangiogenic properties. However, in addition to its well known teratogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(31 citation statements)
references
References 71 publications
1
29
0
1
Order By: Relevance
“…In the present study, we investigated whether thalidomide or lenalidomide were capable of reducing the viability of MCL cells in vitro and whether this effect could be augmented by combining either drug with rituximab. We were unable to demonstrate a direct effect of thalidomide or lenalidomide on MCL cell viability despite using concentrations (50 µg/ml) far exceeding physiological ones (thalidomide 1–4 µg/ml [18]), suggesting that these agents alone are not capable of inducing significant levels of MCL cell death. However, we did find that both drugs indirectly affect viability by enhancing PBMC-mediated toxicity and that lenalidomide induced significantly higher levels of toxicity than thalidomide.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we investigated whether thalidomide or lenalidomide were capable of reducing the viability of MCL cells in vitro and whether this effect could be augmented by combining either drug with rituximab. We were unable to demonstrate a direct effect of thalidomide or lenalidomide on MCL cell viability despite using concentrations (50 µg/ml) far exceeding physiological ones (thalidomide 1–4 µg/ml [18]), suggesting that these agents alone are not capable of inducing significant levels of MCL cell death. However, we did find that both drugs indirectly affect viability by enhancing PBMC-mediated toxicity and that lenalidomide induced significantly higher levels of toxicity than thalidomide.…”
Section: Discussionmentioning
confidence: 99%
“…Thalidomide (a-N-phthalimidoglutaramide) has complex immune-modulatory and anti-inflammatory properties. It has been shown to down-regulate the production of TNF-α and other pro-inflammatory cytokines in monocytes, to inhibit the transcription factor nuclear factor kappa B (NFkB), down-regulate cyclooxygenase 2, and to inhibit angiogenesis [124,125] . One randomized placebo-controlled trial in patients with cancer cachexia showed that the drug was well-tolerated and effective at attenuating loss of weight and lean body mass in patients with advanced pancreatic cancer [126] .…”
Section: Thalidomide and Etanerceptmentioning
confidence: 99%
“…Both cytokines are regulated by thalidomide and CAM. The inhibition of TNF-α is one of the most significant properties of thalidomide by human-activated monocytes [25], and IL-6 is also inhibited by thalidomide treatment [26]. The addition of CAM reduces the levels of TNF-α and IL-6 in several cell types, such as synovial fibroblast-like cells and alveolar macrophages [27,28].…”
Section: Discussionmentioning
confidence: 99%